INVESTIGATE THE RELATIONSHIP BETWEEN HEAD TEACHER ETHICAL LEADERSHIP STYLE AND TEACHER’S MOTIVATION AT SECONDARY LEVEL - Saadia Mussarrat; Dr. Qurat Ul Ain; Sehrish Sarfraz; Umair Mehmood (International Journal of Contemporary Issues in Social Sciences, 2024)
The relationship between a head teacher’s ethical leadership style and teacher motivation at the secondary level is a critical area of educational research. Ethical leadership, characterized by fairness, integrity, and moral guidance, can significantly impact teachers’ motivation. When educators perceive their leaders as ethical, they are more likely to feel valued, engaged, and motivated to excel in their roles. Understanding this dynamic can help educational institutions foster a positive work environment and enhance teaching quality. This study aims to explore the correlation between head teacher ethical leadership styles and teacher motivation within secondary-level educational settings. By examining the influence of ethical leadership behaviors on teacher motivation, this research seeks to provide insights into the potential impact of principled leadership on educators’ job satisfaction, engagement, and overall performance in the secondary school environment. This quantitative and descriptive study investigates ethical leadership among secondary school teachers (SSTs) in District Talagang, comprising both male and female teachers across 120 public secondary schools. The research involved a two-step sampling process, initially piloting with 65 teachers (20% of the total), followed by a final sample of 348 secondary teachers selected from the population. Census sampling technique were adopt because oure sample is whole population. The findings illuminate that a substantial majority of teachers, exceeding 80%, perceive their head teachers as exemplars of ethical leadership. These head teachers are characterized as honest, trustworthy, fair, and just in their actions, effectively modeling ethical behavior. Over 70% of teachers perceive their head teachers as open to feedback and amenable to change. These findings underscore the paramount significance of ethical leadership in secondary schools, emphasizing the value that teachers place on ethical behavior and decision-making by their head teachers. Furthermore, the study unveils a noteworthy positive correlation between head teachers’ ethical leadership style and teacher motivation. Those teachers who view their head teachers as ethical leaders report higher levels of motivation and job satisfaction. Specifically, teachers esteem head teachers who are fair, transparent, and ardently committed to ethical leadership. This indicates that ethical leadership profoundly influences teacher motivation and contributes to a positive school culture. Teachers who perceive their head teachers as trustworthy, transparent, fair, and just express a deeper engagement with their work and stronger connections with colleagues and students. This highlights ethical leadership’s role in nurturing a sense of equity and respect within the school community, propelling teachers to excel in their roles.